The Influence Of Company Size, Profitability And Growth Opportunities On Capital Structure - Yesi Fitri Yuwanita; Desi Ilona; selvi Yona Sari (Universitas Serang Raya, 2020)
The purpose of this study is to determine the effect of company size, profitability and growth opportunity on capital structure. The research object used was a publicly listed company listed on the Indonesia Stock Exchange in 2016-2018. This study uses a random sampling technique in determining research samples. The number of companies selected as samples in this study were 363 companies from 656 publicly listed companies listed on the Indonesia Stock Exchange. The data source used in this study is secondary data. The data analysis method used in this study is panel data regression analysis. The results of this study indicate that simultaneously the size of the company (Size), profitability (ROA) and growth opportunity (GO) with liquidity (CR) as a control variable has a significant effect on capital structure. The size of the company (Size) and growth opportunity (GO) does not significantly influence the capital structure (DER), and profitability (ROA) has a negative and significant effect on the Capital Structure (DER). While liquidity (CR) has a negative and significant effect.